Die dualistische Metaphysik von Jürgen Habermas - Albert, Hans; Justus Liebig University Giessen (My University, 2009)
In contrast to traditional philosophy, Habermas does not view his ‘postmetaphysical thought’ as a conception of reality that claims to be true. Actually, however, his ‘postmetaphysical thought’ is a metaphysical dualism, which stands in opposition to the metaphysical naturalism proposed by other contemporary philosophers. In a specific way, he draws upon the Kantian idea of the constitutive function of reason. He holds, as other constructivists, an idealistic metaphysics that leads him to the construction of an epistemic dualism, contrasting the objective world of the natural sciences with the ‘Lebenswelt’. It turns out that he is unable to solve the problems connected with this view. Metaphysical realism, which avoids these problems, is rejected by him. His ‘postmetaphysical thought’, Habermas tells us, does not presume to decide what is reasonable or not in religious teachings. The core of religious experience, he suggests, is ‘opaque’ and therefore immune to criticism. Faith and knowledge are, as it seems, incommensurable, so that a reasonable critique of religion is impossible. Thus, he consents to an arbitrary restriction of the use of reason, as proposed also by Joseph Ratzinger.
Keywords: ddc:100; ddc:330